Extracted principles and implications from the International Center for Aquatic research annual 1989-1990 - Rushall, B. S.
Adapted from SWIMMING COACHING SCIENCE BULLETIN: Volume 1 Number 6 - December, 1992. The purpose of this Bulletin is to highlight the major principles from each study in the 1989-90 Annual and explain their implications for coaching. Content: PHYSIOLOGICAL STUDIES , TRAINING RESPONSES AND ADAPTATIONS, BIOMECHANICAL STUDIES, PSYCHOLOGICAL STUDIES, NUTRITIONAL STUDIES.